PENGARUH PENAMBAHAN HANDGRIP STRENGTH EXERCISE PADA PEMBERIAN NERVE GLIIDING EXERCISE TERHADAP GEJALA CARPAL TUNNEL SYNDROME - Hidayat Machmud; Ferian Nugraha; Jerry Maratis; Kesit Ivanali (LPPM Universitas Abdurrab, 2025)
Objective: The objective was to determine the effect of adding handgrip strength exercise to nerve gliding exercise on the symptoms of CTS. Method: This study was a quasi-experimental research using a pretest-posttest group design. The sample was taken from the population of Universitas Esa Unggul; 22 people were obtained and divided into 2 groups, with each group consisting of 11 people. Results: Hypothesis I was tested using the Wilcoxon Signed Ranks Test, with a BCTQ Symptom Severty Scale (SSS) value of p = 0.003 and a BCTQ (FSS) value of p = 0.005. Hypothesis II was tested using the Wilcoxon Signed Ranks Test with a BCTQ (SSS) value of p = 0.003 and a BCTQ (FSS) value of p = 0.012. Hypothesis III was tested using the Mann-Whitney U Test with a BCTQ (SSS) value of p = 0.842 and a BCTQ (FSS) value of p = 0.199. Conclusion: There was no difference in adding handgrip strength exercise intervention to nerve gliding exercise in reducing CTS symptoms.